New Papiliotrema laurentii UFV-1 strains with improved acetic acid tolerance selected by adaptive laboratory evolution - Almeida, Eduardo Luís Menezes de (2021)
Depletion of fossil fuels and increase in greenhouse gas emissions have boosted the development of new technologies for biodiesel production. Oil extracted from soybeans is the major source for Brazilian biodiesel production (69.8%); nevertheless, its utilization as feedstock requires arable land, water, and nutrients that could be utilized for food crops and conversion to native vegetation. These drawbacks can be circumvented by using yeast oil for biodiesel production. The oleaginous yeast Papiliotrema laurentii can accumulate a high amount of lipids and metabolize lignocellulose-derived sugars. Due to the recalcitrant nature of lignocellulosic biomasses, a pretreatment step is required. Nevertheless, acid pretreatment, the most used in lignocellulosic biomasses, leads to the formation of toxic compounds that can inhibit yeast growth. Among them, acetic acid is the most abundant, and in its undissociated form diffuses through the cell membrane and dissociates in the cytosol, disrupting cell homeostasis. To circumvent the inhibitor effect, detoxification processes are applied to remove or reduce their concentrations. However, the detoxification strategies applied are usually insufficient to reduce the acetic acid concentration. For this, oleaginous yeasts capable of tolerating acetic acid are of interest. Recently, our research team isolated and characterized a P. laurentii able to achieve the highest lipid contents from xylose as the sole carbon source. Nevertheless, we observed in this work that its growth is severely impaired by acetic acid (1.0 g/L). Therefore, we applied Adaptive Laboratory Evolution (ALE) to select strains of P. laurentii UFV-1 tolerant to acetic acid. We selected and characterized three Acetic acid Tolerant Strains (ATS). All strains evolved displayed the tolerance phenotype (able to grow in the presence of 1.5 g/L of acetic acid) after 398 generations being exposed to increasing concentrations of acetic acid (0.7, 0.9, and 1.5 g/L). However, different phenotypes emerged alongside. Although the acetic acid tolerance presented by ATS II was, along with ATS I, the highest observed in this work, it displayed trade-offs in the absence of the acid. as its lipid productivity, biomass and specific growth rate decreased. ATS I and III showed physiological parameters similar to the parental strain (lipid and biomass production, and sugar uptake) in stress absence. However, the ATS III, in contrast to ATS I, did not display the oleaginousviii phenotype (<20% g lipids/ g DW) when challenged with 1.75 g/L of acetic acid. Therefore, ATS I was the most promising strain, showing tolerance to acetic acid and oleaginous phenotype in all conditions evaluated. Keywords: Yeast. Oleaginous. Inhibitors. Lignocellulosic biomass.